IMPORTANCE PERFORMANCE ANALYSIS DALAM KASUS KEPUASAN KONSUMEN USAHA LAUNDRY - Restu Khaliq (Alhadharah: Jurnal Ilmu Dakwah, 2018)
Importance Performance Analysis (IPA) is one method measuring the gap of service quality attributes according to the consumer's perspective. The application of this method is important in the field of business services such as laundry because some people today are often unable to do daily routine work such as washing dirty clothes. Using laundry services is one solution. This study aims to assess service quality attributes which are divided into two sub-variables (functional quality and technical quality) through Importance Performance Analysis (IPA) in XYZ laundry service businesses. The number of respondents in this study was 72 people. The research questionnaire was distributed to all XYZ laundry customers from July to September 2018. The results of this study indicate that XYZ luandry business is recommended to prioritize service on good delivery of consumer goods, cut down on waiting time for service work, improve employee appearance and try to show business to help.